A harmony of the spirits : translation and the language of community in early Pennsylvania - Erben, Patrick M. (Patrick Michael) (Chapel Hill : Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2012)
In early Pennsylvania, translation served as a utopian tool creating harmony across linguistic, religious, and ethnic differences. This book challenges the long-standing historical myth - first promulgated by Benjamin Franklin - that language diversity posed a threat to communal coherence. It deftly traces the pansophist and Neoplatonist philosophies of European reformers that informed the radical English and German Protestants who founded the 'holy experiment'.
"Unter der Leitung seines Geistes": Spiritual translation in early America -- Reversing the heritage of Babel: Visions of religious and linguistic renewal in seventeenth-century Europe -- Translating Pennsylvania: visions of spiritual community in promotional literature -- Debating Pennsylvania: religious and linguistic diversity and difference -- "Honey-combs" and "paper-hives": Francis Daniel Pastorius and the gathering of a translingual community of letters -- A hidden voice amplified: music, mysticism, and translation -- "What will become of Pennsylvania?": war, community and the language of suffering for peace -- Confusio linguarum redux: Moravian missions, multilingualism, and the search for a spiritual language.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Language and languages -- Variation; Pennsylvania -- History; Pennsylvania -- Languages; Language and culture -- United States; HISTORY / United States / Colonial Period (1600-1775); Language and culture; Language and languages; Language and languages -- Variation; Pennsylvania; United States; LANGUAGE ARTS & DISCIPLINES / Alphabets & Writing Systems; Electronic books; History